The Development of Women’s Shirt for the “Berkain” Trend with the Application of Embroidery - Rajagukguk, Juniar Angelin Berliana; Bastaman, Widia Nur Utami; Putri, Liandra Khansa Utami; Muslikhani, Aghnia Fauzul (Gorga : Jurnal Seni Rupa, 2025)
The emergence of the Berkain trend since 2017, initiated by the Indonesian art community Swara Gembira, has shown a new fashion style. The younger generation combines traditional Indonesian fabrics with modern clothing products, one of which is shirts with decorative embroidery elements. Data shows that many local Indonesian brands offer women's shirts with simple cuts and limited design development. On the other hand, the decorative elements used are still largely inspired by floral motifs with embroidery techniques that lack variety. This presents an opportunity to develop clothing with more diverse embroidery motifs to create new design variations. This research uses a double diamond approach: discover, define, develop, and deliver, with the application of the craft creation development method: inquiry, design, and reification in the develop stage. The final product of this research is a women's shirt with embroidery motifs inspired by traditional Indonesian dance culture so that it can meet the market's need for varied shirt designs and motifs that are still comfortable and casual to wear in daily activities.